Tc99m-sestamibi: pembangunan kit radiofarmaseutikal untuk pemetaan jantung - Wan Hamirul Bahrin W.K.; Mohd Cairul Iqbal M.A; Rosnani H.; Zulkifli M.H; Yahaya T.; Karuppaiya A.; Rasyieda A. (Universiti Kebangsaan Malaysia, 2009)
A development and comparison study of the Nuclear Malaysia’s Tc99m-sestamibi heart imaging agents (NM kits) and the commercial products is reported. Three batches of kits labelled as B1, B2 and B3 were produced by freeze drying technique. The commercial products such as sestamibi Cardiolite, Polatom, ChiMIBI and tetrofosmin Myoview were used in this study. The quality control testing which included microbiology testing, radiochemical and animal biodistribution study were conducted accordingly. The NM sestamibi kits passed the sterility and pirogen test. The Radiochemical Purity testing (RCP) was assessed by the Instant Thin Layer Chromatography (ITLC) and High-Performance Liquid Chromatography (HPLC) methods after the reconstitution of the Tc99m-sestamibi. The RCP results were above 90% and the kits were stable for 52 weeks. The animal biodistribution studies were carried out on Sprague-Dawley rats at 5, 30, 60, 120 and 1440 minutes post injection time intervals. The percentage injected dose per gram organ in heart for Tc99m-B1 were 4.722±0.343%, 3.752±0.438%, 4.564±0.664%, 4.180±1.293% and 1.090±0.230% at 5, 30, 60, 120 and 1440 minutes respectively. This is followed by the Tc99m-B2; 3.852±0.406%, 3.268±0.425%, 3.366±0.316%, 4.324±1.044% and 1.038±0.144%, Tc99m-B3; 5.404±0.351%, 4.818±0.579%, 6.015±0.774%, 5.028±1.353% and 1.623±0.692% at the same time intervals. Independent T Test showed that heart uptake was significant as compared to the control (p<0.05). The biodistribution study also showed that the radiopharmaceuticals localized selectively in the myocardium of rats. The NM sestamibi kits were comparable to the commercial products. Blood, lung, kidney and intestines washout were found to be fast and efficient. The biodistribution and analysis of heart-to-lung and heart-to-liver uptake ratios showed that NM sestamibi kits has a potential and could be used as heart imaging agents.